Plasma Trimethylamine N-Oxide and Its Precursors: Population Epidemiology, Parent–Child Concordance, and Associations with Reported Dietary Intake in 11- to 12-Year-Old Children and Their Parents. Issue 7 (10th June 2020) - Andraos, Stephanie; Lange, Katherine; Clifford, Susan A; Jones, Beatrix; Thorstensen, Eric B; Kerr, Jessica A; Wake, Melissa; Saffery, Richard; Burgner, David P; O'Sullivan, Justin M
Abstract: Background: Trimethylamine N-oxide (TMAO) is a microbiome- and diet-derived metabolite implicated in adverse cardiovascular outcomes. To date, studies of plasma TMAO concentrations have largely focused on individuals with metabolic disease. As such, data on TMAO concentrations in population settings and parent–child dyads are lacking. Objectives: This study aimed to investigate parent–child concordance, age, and sex effects on plasma concentrations of TMAO and its precursors [l -carnitine, choline, betaine, and dimethylglycine (DMG)]. Associations between concentrations of TMAO and its precursors and self-reported dietary intakes of animal protein (i.e., red meat, meat products, chicken, fish, milk products, and cheese) and fast-food meals were also investigated. Methods: A total of 1166 children (mean ± SD age: 11 ± 0.5 y, 51% female) and 1324 parents (mean ± SD age: 44 ± 5.1 y, 87% female) had a biomedical assessment as part of Growing Up in Australia's Child Health Checkpoint. Plasma TMAO and precursor concentrations were quantified using ultra-high-pressure LC coupled with tandem MS. Results: Familial dyads significantly contributed to plasma TMAO and precursor concentrations ( P  < 0.0001), explaining 37% of variance for TMAO concentrations. Least-square mean ± SE plasma TMAO was lower in children (0.79 ± 0.02 µM on the log-scale) than in adults (1.22 ± 0.02 µM). By contrast, children's betaine (40.30 ± 0.34 µM) and DMG concentrations (1.02 ± 0.01 µM on the log-scale) were higher than adults' betaine (37.50 ± 0.32 µM) and DMG concentrations (0.80 ± 0.01 µM) ( P  < 0.0001). Mean values of all metabolites, except adult TMAO, were higher in males than in females ( P  < 0.001). Greater reported intake of red meat and fish was associated with higher TMAO concentrations in both children [estimates (95% CIs) for red meat: 0.06 (0.01, 0.10); fish: 0.11 (0.06, 0.17)] and adults [red meat: 0.13 (0.08, 0.17); meat products: 0.07 (0.03, 0.12); and fish: 0.09 (0.04, 0.14)]. Conclusions: Age, sex, and shared family factors, including diet, contribute to variation in plasma concentrations of TMAO and its precursors. Abstract : Age, sex, and shared family factors characterize the concentrations of plasma TMAO and those of its precursors in Growing Up in Australia's CheckPoint Study of children and adults.